Analysis of the robustness of energy supply in Japan: Role of renewable energy - Danmei Zhu; Seyed Mostafa Mortazavi; Akbar Maleki; Alireza Aslani; Hossein Yousefi (Energy Reports, 2020)
Today, the security of energy has become one of the primary concerns of all the countries around the world due to the limited energy sources, increasing population, energy prices fluctuations and limitations in energy supply. Japan is considered as one of the largest energy consumers and energy importers throughout the world which almost 96% of its primary energy supply in national level relies on the imports from other countries. After experiencing several harsh energy supply conditions over the last 40 years, Japan realized the sensitivity of its energy supply and decided to fundamentally restructure its energy supply and rely more on energy mix diversification, renewable energies, energy efficiency improvement, and carbon emissions reduction. In this article the energy security improvement and the government actions to boost diversification of energy by focusing more on renewable energies and reducing energy intensity, increasing energy efficiency and decreasing energy import dependency in Japan is studied. In addition, various renewable energy technologies as a substitute source of energy and promising ways of domestic energy supply as well as the factors to improve the security of energy supply are studied thoroughly. Moreover, it was realized that the most primary energy sources in Japan are biofuel and waste energy followed by hydropower and geothermal energy respectively.
Keywords: 330; Energy policy; Renewable energy; Energy efficiency; Energy security; Energy supply